1996
DOI: 10.3382/ps.0750335
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nonautoclaved and Autoclaved Water-Soluble Wheat Extracts on the Growth of Clostridium perfringens

Abstract: Clostridium perfringens is the causative agent of necrotic enteritis, a commonly diagnosed disease in chickens that is also observed in turkeys and geese. Two trials were conducted to determine the in vitro effect of filter-sterilized, water-soluble wheat extracts on the growth of C. perfringens. The extracts were either nonautoclaved or autoclaved at 121 C for 40 min and were used to reconstitute thioglycolate broth media. Results of this study suggest that growth of C. perfringens is suppressed in vitro by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We could not confirm why CWPS carbohydrates contents differed when extracted by either the hot buffer or DMSO extraction methods. It has been reported that the Gal and Glc contents of the polysaccharides in the cell walls of wheat were reduced after autoclaving (Branton et al, 1996). Moreover, GXM is typically extracted after heat killing C. neoformans, whereas GalXM and GXMGal can be extracted without heating (Klutts and Doering, 2008;Heiss et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We could not confirm why CWPS carbohydrates contents differed when extracted by either the hot buffer or DMSO extraction methods. It has been reported that the Gal and Glc contents of the polysaccharides in the cell walls of wheat were reduced after autoclaving (Branton et al, 1996). Moreover, GXM is typically extracted after heat killing C. neoformans, whereas GalXM and GXMGal can be extracted without heating (Klutts and Doering, 2008;Heiss et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Branton et al (1996), on the other hand, concluded that C. perfringens growth in TG was suppressed by the addition of wheat extracts compared with deionized water. These differing findings may be explained by the fact that three complete broiler grower diets, with a main constituent of wheat, barley or corn, were used in the present study, compared with a wheat extract alone used by Branton et al (1996). In addition, samples used by Branton et al were heated to 100°C for 24 h prior to adding them to culture media, a process that may have altered the endogenous enzymatic activity in the wheat extract.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that IDF has a greater adsorption capacity than SDF. By autoclaving, the contents such as barley or wheat, amino acids and glycosyl components have been changed (35,36). Similarly, the structure of IDF might have been changed by autoclaving.…”
Section: Discussionmentioning
confidence: 99%